BEI for Creative Industry In Indonesia - Gancar Premananto; Sri Hartini; Jovi Sulistyawan (Journal of Economics, Business, and Accountancy Ventura, 2018)
The purpose of this research is to provide a description of the implementation of ethics business in creative industry in Indonesia. This study focuses on understanding the Business Ethics Index (BEI) in Indonesia, especially for the creative industry in millennial generation perception. This study uses survey method with 136 respondents who are millennial generation. In addition, this research also uses 3 subsectors, namely culinary industry, art industry, and showbiz industry. Sampling is done by accidental sampling. The measurement of BEI is done using 4 dimensions, namely "personal - vicarious" and "past - future". The result of the study shows that millennial generation in Indonesia is open with global culture. From BEI calculation, it is found that BEI value for creative industry both general and specific in Indonesia get the result above 100 equal to developed country. The result of the research shows that there is no significant difference of BEI between subsector of creative industry in Indonesia and BEI each subsector with BEI categorized industry in Indonesia. This can be interpreted that Y / millennial generation in Indonesia is an open generation, they are not sensitive to ethical behavior in the creative industry